Studi Komparatif Komposisi Media Tanam Terhadap Pertumbuhan Tanaman Aglaonema (Aglaonema commutatum) Varietas Lady Gaga - Fadilah, Lya Nailatul; Muda, Strayker Ali; Irmawati, Irmawati; Anggraini, Putri Olivia; Zaidan, Zaidan; Halimi, Entis Sutisna; Ramadhani, Fitri; Lumbantoruan, Santa Maria; Cahya, Muhardianto; Nur, Tri Putri (Agroteknika, 2025)
Aglaonema commutatum or aglaonema is an ornamental leaf plant. In Indonesia, it is populary referred to as Sri Rejeki. Aglaonema variety Lady Gaga has high aesthetic value and demand by many people because its distinctive patterns and colors. The success of aglaonema cultivation is influenced by the composition of growing medium used. This study aims to determine the best planting medium composition through a comparative study. The research was conducted from July to September 2023 in Palembang City. Was arranged based on Randomized Block Design, consisting of three treatments: volcanic sand (M0), volcanic and rice husk 1:1 v/v (M1), and volcanic sand and risk husk 1:2 v/v (M2). The research data were analyzed using Analysis of Variance (ANOVA). The result of this study showed that the use volcanic and rice husk 1:1 v/v (M1) significantly enhanced all growth parameters, including the number of leaves, leaf length, leaf width, and new leaf growth; and parameters related to visual color and quality grade, namely parameters color, brightness, shape and size, also aglaonema leaf motif. In addition, direct sunlight also effect the color, brightness, and leaf motif of aglaonema var. Lady Gaga which is increasingly fading. Therefore, it is recommended that aglaonema cultivation be carried out in shaded areas that not exposed to direct sunlight.